Uncertainty and continuity: preparing for long-term changes to the global economy - Spence, Michael (Henry Stewart Talks, 2025)
Trump administration, US economic policies, Globalism, Trading blocks, Tariffs, Multilateralism, Trade, National security, International interdependence, Trade barriers, Uncertainty, Digital economy and trade, Education, research, and development, Pillars of long-term economic performance